Argumentation Skills of Pre-Service Elementary Teachers on Atmospheric Pressure - Pelin Mete (Universitas Pendidikan Indonesia, 2023)
In the present study, atmospheric pressure, an abstract concept that learners generally have difficulty understanding and explaining, was presented to pre-service elementary teachers (PSTs) with the method of argumentation. The argument levels of the PSTs were examined using the Predict - Observe - Explain (POE) experiments in teaching the subject of